Multiple supernumerary teeth in a non-syndromic pediatric patient: A rare condition - Lévano Loayza, Sandro Alexander (2020)
The presence of multiple supernumerary teeth in the oral cavity is an infrequent alteration of dental development in patients who do not have an associated syndrome, that can induce various alterations such as malocclusions, delay in dental eruption, reabsorption of adjacent teeth, cyst formation, root dilacerations and giroversions. The objective of this clinical case is to report the presence of multiple supernumerary teeth, which caused the ectopic eruption and gyroversion of adjacent teeth, causing a crossbite in the oral cavity of a non-syndromic pediatric patient of the Centro Dental Docente Cayetano Heredia in 2019. The treatment performed was the simple extraction of the erupted supernumerary teeth and the complex extraction with flap of the retained ones.